23. EVALUATE SENSITIVITY AND ANTIBIOTIC RESISTANCE RATE IN PATIENTS WITH PNEUMONIA AND MECHANICALLY VENTILATED PNEUMONIA AT THU DUC CITY HOSPITAL IN THE PERIOD OF 2020 - 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: The study aimed to evaluate antibiotic sensitivity and resistance in patients with VAP and VAP at Thu Duc City Hospital.Methods: The study was conducted on all patients with VAP and VAP from January 1st 2020 to November 31st 2023, with positive sputum culture results and pneumonia appearing after 48 hours of admission or after 48 hours. mechanical ventilation.Results: In 1446 cultured samples, 94 patients were identified with HAP and VAP, with a mortality rate of 48.9%. The most common bacterial strains include A.baumanii (30.8%), Klebsiella pneumonia (22.3%), and P.aeruginosa (10.6%). The susceptibility rate to Cefoperazone/Sulbactam in A.baumanii was 61.5%, while the susceptibility rate to Imipenem and Amikacin was 15.3% and 7.7%, respectively. Acinetobacter spp strains showed complete sensitivity to Cefoperazone/Sulbactam (100%).Conclusion: Regularly updating microbiological data is necessary to select effective antibiotics for treatment.
Keywords: Antibiotic resistance; sensitivity; hospital-acquired pneumonia